Systematic modulation of the lipid composition enables the tuning of liposome cellular uptake. (1st March 2023) - Mateos-Maroto, Ana; Gai, Meiyu; Brückner, Maximilian; da Costa Marques, Richard; Harley, Iain; Simon, Johanna; Mailänder, Volker; Morsbach, Svenja; Landfester, Katharina
Abstract: As liposomes have been widely explored as drug delivery carriers over the past decades, they are one of the most promising platforms due to their biocompatibility and versatility for surface functionalization. However, to improve the specific design of liposomes for future biomedical applications such as nanovaccines, it is necessary to understand how these systems interact with cell membranes, as most of their potential applications require them to be internalized by cells. Even though several investigations on the cellular uptake of liposomes were conducted, the effect of the liposome membrane properties on internalization in different cell lines remains unclear. Here, we demonstrate how the cellular uptake behavior of liposomes can be driven towards preferential interaction with dendritic cells (DC2.4) as compared to macrophages (RAW264.7) by tuning the lipid composition with varied molar ratios of the lipid 1, 2-dioleoyl- sn -glycero-3-phosphoethanolamine (DOPE). Cellular internalization efficiency was analyzed by flow cytometry, as well as liposome-cell membrane co-localization by confocal laser scanning microscopy. The corresponding proteomic analysis of the protein corona was performed in order to unravel the possible effect on the internalization. The obtained results of this work reveal that it is possible to modulate the cellular uptake towards enhanced internalization by dendritic cells just by modifying the applied lipids and, thus, mainly the physico-chemical properties of the liposomes. Statement of significance: In the field of nanomedicine, it is of key importance to develop new specific and efficient drug carriers. In this sense, liposomes are one of the most widely known carrier types and used in clinics with good results. However, the exact interaction mechanisms of liposomes with cells remain unclear, which is of great importance for the design of new drug delivery platforms. Therefore, in this work we demonstrate that cellular uptake depends on the lipid composition. We are able to enhance the uptake in a specific cell type just by tuning the content of a lipid in the liposome membrane. This finding could be a step towards the selective design of liposomes to be internalized by specific cells with promising applications in biomedicine. Graphical abstract: Image, graphical abstract